Effect of Herbicide on Weed Management in Potato - Amarananjundeswara, H.; Prasad, P. S.; Shetty, Soumya; Sandhya, G. C. (International Journal of Economic Plants, 2021)
A field experiment was conducted under All India Co-ordinated Research Project on Potato at Horticulture Research and Extension Centre (HREC), Hassan, Karnataka consecutively for three years during Kharif season of 2014, 2015 and 2017 to study the effect of herbicide on weed management in potato cv. Kufri Jyoti. Weed management is a major component in potato production and has been accomplished using different methods. In the experiment both manual and chemical methods were adopted to control weeds in potato. An experiment was laid out in Randomized Complete Block Design with four replications by following standard spacing of 60×20 cm2. In this study, treatments with hand weeding at 30, 40 and 50 days interval and metribuzine as both pre-emergent and post emergent herbicide were sprayed. Among the seven different treatments, pre-emergent spray of metribuzin @ 0.75 kg ha-1 (1 g l-1) at planting of tubers recorded highest marketable tuber yield of 12.32 t ha-1 and total tuber yield of 14.29 t ha-1 with benefit cost ratio of 1.55 followed by the treatment with post-emergent spray of metribuzin @ 0.75 kg ha-1, which was documented marketable tuber yield of 11.79 t ha-1 and total tuber yield of 13.71 t ha-1 with benefit cost ratio of 1.48. Hence, metribuzin @ 0.75 kg ha-1 (1 g l-1) can be used as an effective herbicide for the management of weeds in potato cultivation under Southern Dry Zone of Karnataka.